(untitled) (Bangladesh Journal of Infectious Diseases, 2020)
Background: Encephalitis is an acute inflammatory process that affects brain tissue and is almost always accompanied by inflammation of the adjacent meninges. The disease is most commonly caused by viral infection. Objective: The purpose of the present study was to determine the clinical and cerebrospinal fluid profile of childhood encephalitis and to document Herpes simplex antibody status in cerebrospinal fluid. Methodology: This descriptive analytical study was conducted in Department of Paediatrics of Shaheed Suhrawardy Medical College Hospital and Dhaka Medical College Hospital from May 2011 to October 2011. A total of 30 children of encephalitis were included in this study. Cerebrospinal fluid (CSF) routine and Herpes Simplex virus (HSV) antibody in CSF were done to all patient. Result: Fever and convulsion was found in 29(96.7%) and 28(93.3%) cases respectively in studied patients. Altered level of consciousness was present in 29(96.7%) cases. Fever, convulsion and altered level of consciousness was statistically significant (p<0.05). Glasgow coma scale (GCS) between 4 to 8 was found in 27 (90%) cases. Signs of meningeal irritation and cranial nerve palsies was found in 9 (30%) and 4 (13.3%) cases respectively. Exaggerated deep reflex was found in 23 (76.6%) cases whereas diminished deep reflex was found in 7 (23.3 %) cases. In cytological study of CSF, lymphocyte was found in 28 (93.3%) patients. Raised protein was found in 16(53.3%) and normal in 14 (46.7%) cases. Among the 30 studied cases 9(30%) cases were IgG positive for HSV, 21 (70.0%) were IgG negative and none were IgM positive. Conclusion: Fever, convulsion, altered sensorium and low GCS were common clinical profile in children. Normal colour, increase lymphocyte count, normal sugar level were significant findings in CSF study. Bangladesh Journal of Infectious Diseases 2020;7(1):8-11